Dioxacyclophanes as a Scaffold for Silicon-based Circularly Polarized Luminescent Materials. Issue 16 (18th April 2019) - Yamanoi, Yoshinori; Usuki, Tsukasa; Omoto, Kenichiro; Shimada, Masaki; Koike, Hikaru; Iwamura, Munetaka; Nozaki, Koichi; Saito, Daisuke; Kato, Masako; Nishihara, Hiroshi
Graphical abstract: Highlights: Planar chiral organosilanes were prepared from dioxacyclophane as a building block. Absolute configurations were determined by single-crystal X-ray analysis. (+)-( R )-2 exhibited circularly polarized luminescence for a small organic molecule. Abstract: Planar chiral dioxacyclophanes were designed and synthesized as a key scaffold for materials with circularly polarized luminescence (CPL). Representative planar chiral 1, 12-dioxa[12](1, 4)naphthaleneophane-derived organosilane compounds (−)-( R )-1, (+)-( R )-2, and (−)-( R )-3 were prepared by (+)-sparteine-mediated aryl metalation and an electrophilic reaction with chlorosilanes. The absolute configurations of the planar chirality were determined in the R form by single-crystal X-ray analysis. Optically active compound (+)-( R )-2 exhibited blue fluorescence and a CPL signal with a dissymmetry factor ( g lum value) of 0.001 in solution. The electronic structure was corroborated by DFT and TD-DFT calculations rationalizing the observed spectroscopic properties.